Teacher’s Strategies in Improving Student’s Reading Interest - Rio Laksamana Prastya; Ashadi Ashadi (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2020)
Most of Indonesian students in university had low interest in reading. Thus, the strategies of the teacher were essential to be considered to build up students’ reading interest. The aim of this research was to investigate the teacher’s strategies in university in teaching reading and also tried to explore the students’ response toward the strategies. Therefore, this research used mix method to reveal the result. The participants involved in this research were 50 master degree students in English Education Department in certain University in Yogyakarta. To acquire the distribution of the students’ response toward the teachers’ strategies, this research used questionnaire. Furthermore, to collect the data deeper, this research used in-depth interviews. The finding showed that the teacher could boost students’ interest in reading if the teacher could provide transparent scoring system which could assist them to obtain a reflection. Therefore, indirectly, by using this strategy, the teacher forced the students to read to acquire good score in reading activity. Thus, the teacher could enhance the students’ reading interest if the teacher could combine transparent scoring system and force in reading class.